Uma nova perspectiva de balneabilidade: redefinição paramétrica e metodológica como ferramenta de gestão da água e sustentabilidade - MACIEL, Allan Costa e Silva (Universidade Federal do Pará, 2018)
This study is intended to address a new vision of bathing, through the redefinition of parametric criteria, the water monitoring and the socioeconomic importance of the monitored site. The actual legislation, CONAMA Resolution No. 274/2000, is outdated and limited with respect to health risks related to the use of waters for recreation and for the environment. Still, we tried to show that the monitoring of water resources through this new approach will serve as a tool for water management as well as for local sustainable economic activities. As case study, the Fazendinha Beach, Macapá/AP, has been selected. Therefore, sampling and analysis were performed in twofold manner: (i) to demonstrate the importance of integrating new parameters in the assessment of bathing suitability, and (ii) socioeconomic and environmental research in Fazendinha Beach to collect information from users, owners of commercial establishments (bars, restaurants, etc.) and street vendors to evaluate the economic sustainability of local leisure activities. The results, mainly the socioeconomic research, revealed an intense relationship between the local community and that beach.